Beyond stress and burnout: psycho-spiritual innovation and pastoral accountability in frontline care for emergency response workers and police - Devenish-Meares, Peter (Ushus Journal of Business Management, 2026)
This paper explores innovation and accountability in spiritual and pastoral care for frontline personnel facing chronic stress, trauma, and moral injury. Police, medical and emergency service workers operate within stressful and morally charged environments where trauma, psychosocial safety and recovery are constant challenges. Amid such pressures, there is a vital need for credible, evidence-informed, yet deeply human psycho-spiritual frameworks that protect confidentiality while promoting care and wellbeing. Using a Critical Interpretive Synthesis enriched by heuristic and bricolage perspectives, this study integrates recent research across psycho-spirituality, positive psychology, and occupational health. It demonstrates how pastoral carers, particularly chaplains, co-lead moral repair, meaning-making, and value realignment within a biopsychosocial-spiritual (BPSS) framework. From this synthesis emerges a new psycho-spiritual self-care model anchored in humility, self-compassion, and meaningful detachment as virtues that buffer burnout, reduce harsh self-talk, and foster relational safety. Key innovations include early, embedded pastoral interventions; clear referral pathways with clinical partners; and virtue-based micro-skills that complement psychology and medicine while maintaining the integrity of spiritual presence, ritual, and trust. The paper also addresses the enduring tension between institutional demands for measurable outcomes and the ineffable nature of pastoral impact. It proposes blended evaluation indicators such as moral-injury scales (MIOS/MISS-M), spiritual wellbeing tools (FACIT-Sp-12), alliance markers, and organizational climate measures, interpreted heuristically to safeguard authenticity and confidentiality. By reframing pastoral care and chaplaincy as both evidence-informed and spiritually grounded, this paper offers a transformative model for psycho-spiritual care that renews moral resilience and meaning in high-risk professions. Finally, future research possibilities and limitations are also discussed.